O psoch a l'ud'och - Suchy, Miso (Slovakia, 1993)
In 1988 when Miso Suchy immigrated to America, he did not know a word of English. The film "About Dogs and People" reflects his experiences with "the mute," and is filmed almost without words. Dogs are mute animals, yet according to the director they can tell a lot about the society in which they live. This metaphorical film shows the accuracy of the saying that dogs are a reflection of the people who owe them.
Duration: 00:44:00
Keywords: Documentary films